TUGAS DAN FUNGSI MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN - Suarga , (Idaarah: Jurnal Manajemen Pendidikan, 2019)
In particular the duties and functions of educators and education staff are based on Law No. 14 of 2007, namely as agents of learning to improve the quality of national education, development of science, technology, art, and service to the community. In article 6, it is mentioned: the position of teachers and instructors as professionals to implement the national education system and realize the goals of national education, namely developing the potential of students to become human beings who believe and to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, as well as being a citizen who is supported and responsible. Management of education staff to utilize effective and efficient education personnel to achieve optimal results but still in pleasant conditions